Frequency of and Factors Associated with Emergency Department Intracranial Pressure Monitor Placement in Severe Pediatric Traumatic Brain Injury - Kannan, Nithya (Brain Inj, 2017)
OBJECTIVE: To examine the frequency of and factors associated with emergency department (ED) ICP monitor placement in severe pediatric TBI. METHODS: Retrospective, multicenter, cohort study of children<18 years admitted to the ED with severe TBI and intubated for >48 hours from 2007–2011. RESULTS: 224 children had severe TBI and 75% underwent either ED, operating room (OR) or pediatric intensive care unit (PICU) ICP monitor placement. 4/5 centers placed ICP monitors in the ED, mostly (83%) fiberoptic. Nearly 40% of patients receiving an ICP monitor had it placed in the ED (29% overall). Factors associated with ED ICP monitor placement were: age 13 to<18 years olds compared to infants (aRR 2.02;95% CI 1.37, 2.98), longer ED length of stay (LOS)(aRR 1.15;95% CI 1.08, 1.21), trauma center designation pediatric only I/II compared to adult/pediatric I/II (aRR 1.71;95% CI 1.48, 1.98) and higher mean pediatric TBI patient volume (aRR 1.88;95% CI 1.68, 2.11). Adjusted for center, higher bedside ED staff was associated with longer ED LOS (aRR 2.10;95% CI 1.06, 4.14). CONCLUSION: ICP monitors are frequently placed in the ED at pediatric trauma centers caring for children with severe TBI. Both patient and organizational level factors are associated with ED ICP monitor placement.